The Influence of Islamic Ethical Behaviour and Customer Satisfaction on Customer Trust (A Survey on Islamic Boarding Students of Daarut Tauhiid Bandung) - Sukma Nugraha; Agus Rahayu; Disman Disman; Lili Adi Wibowo; Khania Teresa Gunawan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study aims to analyze the influence and description of Islamic ethical behavior and customer satisfaction on customer trust at the Daarut Tauhiid Islamic Boarding School (PPM DT) students in Bandung. This study uses a descriptive and verification method with a quantitative approach. The research sample consisted of 200 respondents who were PPM DT students who had participated in the program for 1 year (PPM), 2 years (PPML) or less. The data was processed statistically with the Structural Equation Modeling (SEM) method. The results show that the variable Islamic ethical behavior has an indirect and significant effect on customer trust, customer satisfaction has a direct and significant effect on customer trust and Islamic ethical behavior has a direct and significant effect on customer satisfaction. These findings indicate that the application of good Islamic ethical behavior in student boarding schools will encourage customer trust through customer satisfaction for the students of the Daarut Tauhiid Islamic Boarding School Program in Bandung.